The Development and Characterization of Pre-Clinical Models to Advance Cardiovascular Disease Research - Duffy, Breanna. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Lauren Black.; Committee: David Kaplan, Kareen Coulombe, and Navin Kapur.; Keyword: Biomedical engineering.